Elevated Calf Mortality and Long-Term Responses of Wild Bottlenose Dolphins to Extreme Climate Events: Impacts of Foraging Specialization and Provisioning - Mann, Janet; Foroughirad, Vivienne; McEntee, Molly H. F.; Miketa, Madison L.; Evans, Taylor C.; Karniski, Caitlin; Krzyszczyk, Ewa; Patterson, Eric M.; Strohman, John C.; Wallen, Megan M. (Frontiers in Marine Science, 2021)
As demands for wildlife tourism increase, provisioning has become a popular means of providing up-close viewing to the public. At Monkey Mia, Shark Bay, Australia, up to five adult female Indo-Pacific bottlenose dolphins (Tursiops aduncus) visit a 100 m stretch of beach daily to receive fish handouts. In 2011, a severe marine heatwave (MHW) devastated seagrass and fish populations in Shark Bay. Offspring survival declined precipitously among seagrass specialists (dolphins that forage disproportionately in seagrass habitat). As all provisioned dolphins at the site are seagrass specialists, we examined how provisioned and non-provisioned seagrass specialists responded to the MHW. Using 27 years of data we compare habitat use, home range size, calf mortality, and predation risk between provisioned and non-provisioned females and their offspring before and after the MHW. Our results show that provisioned females have extremely small home ranges compared to non-provisioned females, a pattern attributable to their efforts to remain near the site of fish handouts. However, weaned offspring (juveniles) born to provisioned females who are not provisioned themselves also had much smaller home ranges, suggesting a persistent maternal effect on their behavior. After the MHW, adult females increased their use of seagrass habitats, but not their home range size. Provisioned females had significantly lower calf mortality than non-provisioned females, a pattern most evident pre-MHW, and, in the first 5 years after the MHW (peri-MHW, 2011–2015), calf mortality did not significantly increase for either group. However, the ecosystem did not recover, and post-MHW (2016–2020), calf mortality was substantially higher, regardless of provisioning status. With few survivors, the impact of the MHW on juvenile mortality post-weaning is not known. However, over three decades, juvenile mortality among offspring of provisioned vs. non-provisioned females did not statistically differ. Thus, the survival benefits accrued to calves in the provisioned group likely cease after weaning. Finally, although shark attack rates on seagrass specialists did not change over time, elevated predation on calves cannot be ruled out as a cause of death post-MHW. We discuss our results as they relate to anthropogenic influences on dolphin behavioral plasticity and responses to extreme climate events.